SUATU PENELITIAN TENTANG KEMAMPUAN SISWA KELAS DUA SMA 2 TAMBANG DALAM MENULIS TEKS PENGUMUMAN - Fatmi Oktari; Effendy Gultom; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to find out the second year students’ ability of SMA 2 Tambang in writing announcements. This research focuses on grammar, vocabulary, mechanic, form, and fluency based on writing announcements. The instrument used by the writer to collect the data for this study is writing test, that is writing announcements. Based on the research finding in SMA 2 Tambang, it can be found that, first, the ability of the students in writing announcements is in good level. Second, the students’ mean score in grammar is 63, vocabulary is 68, mechanic is 65, fluency is 56, and form is 54.The highest score obtained by the students for vocabulary that in at good level, and the lowest score that the students got is for form at in mediocre level.Keywords: Ability, Writing, Announcements.